Physical activity profile of the Iranian population: STEPS survey, 2016 - Farnam Mohebi; Bahram Mohajer; Moein Yoosefi; Ali Sheidaei; Hossein Zokaei; Bahman Damerchilu; Ashkan Mehregan; Nazila Shahbal; Kamyar Rezaee; Maryam Khezrian; Ali Nematollahi Dehmoosa; Ezzatollah Momen Nia Rankohi; et al. (BMC, 2019)
Abstract Background Insufficient physical activity (IPA) is one of the leading causes of premature mortality through the increased burden of non-communicable diseases. From 1990 to 2017, the percentage of low physical activity attributable disability-adjusted life years (DALY) increased globally by 1.5 times and 2-fold in Iran, causing more than 1.2 million deaths worldwide and 18,000 deaths in Iran in 2017. Reports suggest that Iran, a developing middle-income country, suffers from a high level of IPA. Socioeconomic and cultural alterations along with the country's developments expose the population to IPA risk. We aimed to describe IPA prevalence in Iran's adult population, categorized by demographics, geographical region, and activity domains to assess the present pattern of physical inactivity and its domains in the country. Methods In 2016, in order to represent Iran's adult population, adult participants (n: 30541) from 30 provinces were selected using systematic proportional to size cluster sampling. Physical activity (PA) was assessed via the Global Physical Activity Questionnaire, calculating the Metabolic Equivalent of Task (MET) value in minutes per week for work, recreation, and transport domains. Insufficient physical activity (IPA) was defined according to WHO's recommendation (less than 600 METs per week). Adjusted odds ratios of IPA associates for sociodemographic, lifestyle related variables, and metabolic risk factors were reported. Results A high prevalence of IPA was seen in the total population (54.7%, 95%CI: 54.0-55.3) with a considerable difference between the two genders (males: 45.3% (95%CI: 44.3-46.3); females: 61.9% (95%CI: 61.0-62.7)). Work-related activity was the domain with the greatest percentage of total PA, whereas, both genders lacked recreational activities. In our findings, being female, a housekeeper, younger and living in urban areas were significantly associated with higher levels of IPA. Moreover, insufficient fruit and vegetable consumption, lack of alcohol consumption, having a personal vehicle, and finally, having a medical history of diabetes were significantly associated with the presence of IPA in our population. Among the study population, 33.6% (95%CI: 33.0-34.2) had at least 4 h of sedentary behavior in a typical day. Conclusions Widespread IPA among the Iranian adult population is of major concern. In our findings, we observed a considerable gap in the prevalence and pattern of IPA between the two genders. Additionally, IPA was associated with living in urban areas, unhealthy lifestyle habits and a history of other metabolic risk factors. Thus, a prompt initiative for population-specific actions should be taken.